Implementation of hepatitis C cure in Australia: one year on - Jacqueline A. Richmond; Jack Wallace (Elsevier, 2018)
Objectives: Direct-acting antivirals (DAAs) for the treatment of hepatitis C (HCV) became universally available in Australia in March 2016, with an aim to achieve HCV elimination. Fourteen per cent of Australians with HCV have initiated treatment. The objective of this study was to explore and identify challenges and enablers that have emerged during this initial phase of HCV cure implementation. Methods: Key stakeholders (KS) in primary care, non-government and government sectors were recruited to participate in a telephone-based semi-structured interview to describe challenges and enablers facing individuals with HCV and the healthcare system in implementing HCV cure. Data were thematically analysed. Results: Eleven KS participants were interviewed with each commending the significantly increased numbers of people accessing HCV treatment since March 2016. There was concern that this momentum was waning and that targeted interventions to normalise HCV treatment within primary care were needed. Furthermore, workforce development activities needed to acknowledge the priority of HCV elimination, and develop training and resources for clinicians, most of whom had limited HCV experience. The role of professional champions and multidisciplinary teams of both clinical and non-clinical workers was identified as critical for services that had cured a significant number of people with HCV. Conclusions: Australia has many of the essential elements necessary to eliminate HCV, including universally funded DAA access and multiple treatment access points through primary care. Additional systematic activity is needed to ensure that the DAA-access momentum is maintained and HCV elimination achieved.